MOTIVASI KERJA DENGAN PERILAKU CARING PERAWAT - Merdiana; Astuti Purnamawati, Ditha; Pradika, Jaka (Jurnal Riset Keperawatan dan Kesehatan, 2024)
ABSTRACT Background: Motivation drives and sustains individual performance. In nursing, caring is a core element of professional service. Low levels of caring behavior among nurses may arise from multiple factors, particularly low work motivation. High work motivation is essential for nurses to deliver competent care and ensure patient satisfaction. Conversely, insufficient motivation may hinder clinical decision-making and affect the quality of caring behavior toward patients. Objective: This study aimed to determine the correlation between work motivation and caring behavior among nurses in the Inpatient Department of Landak Regional General Hospital. Methods: This research employed a quantitative correlational analytic design with a cross-sectional approach to examine the relationship between work motivation and caring behavior. The population comprised 108 nurses working in the inpatient department, with 52 participants selected using purposive sampling. Data were collected through structured questionnaires assessing motivation and caring behavior. Data analysis was performed using the Spearman Rank correlation test. Results: Findings indicated that 59.6% of nurses demonstrated good levels of work motivation, while 90.4% exhibited good caring behavior in the inpatient department. Conclusion: There is a statistically significant correlation between work motivation and caring behavior among implementing nurses in the Inpatient Department of Landak Regional General Hospital (p = 0.000 < α = 0.05). These results suggest that higher work motivation is associated with better caring behavior, emphasizing the importance of motivational enhancement programs to improve the quality of nursing care and patient satisfaction.